Acknowledging the distinct cultural nuances in the exchange between the physician and patient in conventional Chinese medicine. - LIU CONG, LIU CONG; DR SURIYAKALA, DR SURIYAKALA (International Journal of Multidisciplinary Research and Studies, 2024)
Chinese medicine has not only been challenged by debates over its efficacy in comparison to Western medicine but also by wars brought on by globalisation. For example, the Wall Street Journal reports that the Nobel Prize committee, when discussing TuYouyou, the first Chinese woman to win a Nobel Prize in chemistry for developing Chinese medicine to treat malaria, gives more credit to modern technology inspired by plant-based treatment than it does to traditional Chinese medicine.” However, because of its growing popularity across the world, researchers are starting to examine the medical, cultural, and communicative success of TCM in China and the West. In order to better understand how some of TCM's basic principles and important values are being lived and displayed in and within the profession, researchers in China will monitor TCM practitioners in their interactions with patients. This study proposes to use a discourse analytic approach supplemented by anthropological field notes and interviews to examine video recordings of practitioner-patient interactions during TCM practise sessions such acupuncture, Chinese herbal medicine prescription, and TCM massage or tuina. The purpose of this research is to gain a better understanding of how "healing, quiet, and the miracle cure" manifest themselves in patient contacts at the clinic.